Percutaneous carotid artery stenting: a strategy in evolution - Kovacic, J. C.; Roy, P. R.; Baron, D. W.; Gunalingam, B.; Muller, D. W. M. (Internal medicine journal, 2005)
Background:  Carotid stenting was initially proposed as an alternative to surgical endarterectomy for selected high‐risk patients. More recently, patients of standard surgical risk are being considered for percutaneous treatment of their carotid disease. Aims:  To describe the clinical outcomes of an initial consecutive cohort of patients treated by carotid stenting at one institution. Methods:  Between December 1997 and July 2003, 111 patients underwent stenting of 118 carotid arteries. Peri‐procedural and long‐term outcome data were collected. Results:  Most patients (>70%) were high‐risk candidates for endarterectomy. Stents were successfully placed in 117/118 carotid arteries (99.2%). Distal protection devices were used in 43/118 (36.4%). The peri‐procedural rate of death or disabling stroke was 3/118 (2.5%). Death or any stroke occurred in 11/118 (9.3%). However, only 7/118 (5.9%) procedures resulted in death or any persistent stroke (neurological deficit >1 week post‐procedure). No myocardial infarction occurred. Median length of post‐procedure hospitalization was 1 day. Long‐term follow up was possible for 101 patients (91.0%) over a mean period of 27.1 months. The Kaplan–Meier estimate of survival free of ipsilateral stroke 36 and 66 months after carotid stenting was 77.0 ± 9.5% and 68.2 ± 15.1%, respectively. The estimated survival free of any stroke or stent failure was 70.9 ± 10.7% and 60.7 ± 17.4%, respectively. The majority of late deaths (7/11) were due to cardiac disease. Conclusion:  We conclude that stenting of carotid stenoses is feasible, with a high procedural success rate and low complication rate. Carotid stenting should be considered the procedure of choice for high‐risk patients. (Intern Med J 2005; 35: 143–150)